5-fluorouracil-induced apoptosis and altered expression of apoptosis-regulating proteins in a model system for multistage cervical carcinogenesis - Mo, Bilan, 1973- (2000)
Thesis (M.Sc.)--Memorial University of Newfoundland. Medicine Bibliography: leaves 184-211 Cervical cancer is the second most frequent cancer among women in the world. It develops by a multistage pathogenesis. However, the molecular mechanism of cervical carcinogenesis remains unclear. Apoptosis, or programmed cell death, has received widespread attention during the past decade due to its essential role as an effective defense against the emergence of cancer. Anticancer agents are effective through the induction of apoptosis specifically in cancer cells. 5-Fluorouracil (5-FU) is a commonly used, effective anticancer drug. In addition, our laboratory has developed a model system for multistage cervical carcinogenesis. To obtain a better understanding of how the progression of cervical cancer may occur in women, we studied whether and how 5-FU may differentially induce apoptosis in the multiple cellular stages. -- To determine whether 5-FU induces apoptosis in our multistage model system composed of primary human ectocervical cells (HEC), HPV 18-immortalized HEC (HEC-18), and CSC-transformed HEC-18 cells (HEC-18T), we treated these cells with 5-FU. 5-FU induced apoptosis in HEC, HEC-18, and HEC-18T, as evidenced by morphologic changes, DNA ladder formation, and flow cytometry analysis. Growth inhibition assay results further indicated that 5-FU-induced apoptosis occurred in a dose-and time-dependent manner. In addition, comparison of HEC with HEC-18 and HEC-18T revealed that both of the latter cell lines were less sensitive to 5-FU-induced apoptosis than HEC when cultured in serum-free medium KGM. However, a higher level apoptosis induced by 5-FU was observed when HEC-18 and HEC-18T were grown in serum-containing medium DMEM compared with KGM. -- The expression level of apoptosis-regulating proteins without treatment with apoptotic stimuli is known to correlate with the sensitivity of cells to apoptosis. To examine whether such a correlation exists in our model system for multistage cervical carcinogenesis, a panel of apoptosis-regulating proteins was analyzed by Western blot analysis without 5-FU treatment. The results revealed that the levels of pro-apoptotic p53, Bak, and Bax proteins were lower in HEC-18 and HEC-18T compared to those in HEC, whereas anti-apoptotic Bcl-2 and BAG-1 p33 isoform, but not Bcl-xL and BAG-1 p50, p46 and p29, were found in enhanced levels. These findings suggest that immortalization by HPV 18 results in decreased sensitivity to 5-FU-induced apoptosis, possibly due to underexpression of pro-apoptotic proteins and overexpression of specific anti-apoptotic proteins. On the other hand, pro-apoptotic p53 and Bax, but not Bak, showed higher expression levels in HEC-18 and HEC-18T in DMEM than KGM, whereas anti-apoptotic Bcl-2, but not Bcl-xL and BAG-1 isoforms, was lower in expression. These findings suggest that the two media differentially affect the sensitivity of cells to 5-FU-induced apoptosis, possibly involving the overexpression of p53 and Bax pro-apoptotic proteins and underexpression of anti-apoptotic Bcl-2. -- Apoptosis is of special interest for chemotherapy for human cancers. Extensive studies have been performed towards the understanding of the mechanism for the initiation of apoptosis. Various apoptosis-regulating proteins have been identified and studied. To investigate whether the expression of apoptosis-regulating proteins is involved in the initiation of apoptosis induced by 5-FU treatment, a panel of such proteins was assayed by Western blot analysis in 5-FU-treatedHEC-18 and HEC-18T grown in DMEM. Of the apoptosis-regulating and related proteins, p53, p53 target proteins p21 and PCNA but not MDM-2, and Bak but not Bax displayed enhanced expression, whereas anti-apoptotic Bcl-2 and BAG-1, but not Bcl-xL, exhibited decreased expression. These results suggest that the dysregulated expression of certain apoptosis-regulating proteins is involved in the initiation of 5-FU-induced apoptosis. -- Resistance to anticancer agents is the major limitation to chemotherapy for cancers. It has become clear that the sensitivity of cells to apoptosis reflects the sensitivity to being killed by anticancer drugs. Therefore, any method that can increase the sensitivity of cells to apoptosis may be effective in chemotherapeutic strategies. As described above, higher susceptibility of HEC-18 and HEC-18T to 5-FU-induced apoptosis was observed when the medium used was DMEM instead of KGM. To study in more detail methods to increase susceptibility to apoptosis, low-density lipoproteins (LDL) or elevated Ca2+ concentration was employed to study the factors involved in the difference between susceptibility to apoptosis in KGM versus DMEM. Both HEC-18 and HEC-18T exhibited more apoptosis induction by 5-FU treatment when they were cultured in KGM plus LDL than in only KGM or KGM plus Ca2+. This suggests that elevated delivery of 5-FU may play an important role in the differential sensitivity to apoptosis in the two media. Furthermore, both Western blot analysis and flow cytometry results showed that differential expression of LDL receptor on cell surfaces was not involved in the differential apoptotic response. -- In summary, this study showed that 5-FU induces apoptosis in our model system for multistage cervical carcinogenesis, discovered that expression level changes of apoptosis-regulating proteins correlate with sensitivity changes of cells to 5-FU-induced apoptosis, implied how 5-FU-induced apoptosis might be initiated and regulated in human ectocervical cells, and also provided information suggesting a feasible approach for clinical application of 5-FU in cervical cancer chemotherapy.